The geomorphological associated of Sebkha in the Mesopotamia- plain of Iraq - أ.م.د.ثائر مظهر فهمي أ.م.د.هالة محمد عبد الرحمن م.م.زينب ضمد حسن (College of Education for Women, 2019)
The Sebkha of geomorphological aspects of evaporative where climate leads active role, which forms part of the earth's surface in the form of Iraqi Mesopotamia plain who of the most fertile land, and because of natural factors and human Common turned most of the arable land to the territory of Sebkha. It was to determine the exact geomorphological associated of Sebkha formats by field work such as: Alnbaka, lakes, salt flats, and other forms of Small is: bridges salt, mud cracks, salt ponds, Rectangles and polygons salt, Sahaf salt, salt domes, salt gravel, bumps saline (salt points), Ash salt, salt bows, in detail and accurately documented Terrestrial Photogrammetry field and were compared to the levels and standards varieties have been selected carefully to identify the characteristics depart with their Global Positioning System The work associated with the geomorphological map shapes of Sebkha.